2020
DOI: 10.1016/j.marpetgeo.2020.104449
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum emplacement inhibits quartz cementation and feldspar dissolution in a deeply buried sandstone

Abstract: Whether the emplacement of petroleum in sandstone reservoirs can preserve porosity during burial remains controversial. In the Kessog Field, UK Central North Sea, average porosities of the crestal sections of the fluvial-deltaic Pentland Formation reservoir can exceed 25 % despite burial to 4 km or more. The predicted porosity for the reservoir at this depth is only around 14 % based on regional data. Oil saturation data, thin-section point counts, grain-size and sorting measurements, reservoir pressure, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The solid negative correlations between IGOI and the average capillary pressure and entry pressure also indicate growth of the lipophilicity of the pore channel, which decreases the capillary and displacement pressure. Similar phenomena have been reported by other scholars for tight sandstone in the Kuqa Basin and Ordos Basin(Lu et al, 2018;Xia et al, 2020).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The solid negative correlations between IGOI and the average capillary pressure and entry pressure also indicate growth of the lipophilicity of the pore channel, which decreases the capillary and displacement pressure. Similar phenomena have been reported by other scholars for tight sandstone in the Kuqa Basin and Ordos Basin(Lu et al, 2018;Xia et al, 2020).…”
supporting
confidence: 91%
“…Hydrocarbon emplacement, in most cases, suppressed the precipitation of carbonate cement (Xia, Wilkinson, & Haszeldine, 2020). Our above analysis showed that the first‐stage ferrocalcite cementation was associated with the first‐stage hydrocarbon emplacement (Figure 10; Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high matrix content is an important reason for severe mechanical compaction. Under compaction, the matrix was squeezed into small pores and throats, which led to extensive plugging of primary pores and tremendous degradation of permeability [47]. Meanwhile, ductile particles form a large number of pseudo-matrices during compaction associated with meteoric water leaching, which further promoted the compaction-induced damage to the reservoir [47].…”
Section: Compactionmentioning
confidence: 99%
“…Under compaction, the matrix was squeezed into small pores and throats, which led to extensive plugging of primary pores and tremendous degradation of permeability [47]. Meanwhile, ductile particles form a large number of pseudo-matrices during compaction associated with meteoric water leaching, which further promoted the compaction-induced damage to the reservoir [47]. The primary porosity was computed empirically using the sorting coefficient that was obtained from the grain size analysis.…”
Section: Compactionmentioning
confidence: 99%